2021
DOI: 10.1001/jamanetworkopen.2021.33073
|View full text |Cite|
|
Sign up to set email alerts
|

Communication of Intent to Do Harm Preceding Mass Public Shootings in the United States, 1966 to 2019

Abstract: IMPORTANCEUnderstanding the motivation of a mass shooter's intent to do harm can help practitioners and policy makers develop more effective intervention strategies. OBJECTIVE To examine the prevalence of communication of intent to do harm, known as leakage, in a sample of 170 mass public shooters from 1966 to 2019; the characteristics of perpetrators who do and do not leak their plans; and whether leakage is a form of fame-seeking behavior or a cry for help among individuals who are in crisis or suicidal. DES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(101 citation statements)
references
References 29 publications
3
98
0
Order By: Relevance
“…This study draws on one of the largest and most comprehensive databases of mass shootings in the United States. Built over three years using public records and open-source data with funding from the National Institute of Justice, The Violence Project Database of Mass Shootings in the United States captures all public mass shootings with four or more victims killed from 1966 to 2020 (Peterson & Densley, 2019). A total of 168 mass shootings were identified involving 172 mass shooters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study draws on one of the largest and most comprehensive databases of mass shootings in the United States. Built over three years using public records and open-source data with funding from the National Institute of Justice, The Violence Project Database of Mass Shootings in the United States captures all public mass shootings with four or more victims killed from 1966 to 2020 (Peterson & Densley, 2019). A total of 168 mass shootings were identified involving 172 mass shooters.…”
Section: Methodsmentioning
confidence: 99%
“…Mass shootings are statistically rare, insomuch that they account for fewer than 1% of all firearm homicides in the United States (Peterson & Densley, 2019), yet they are an almost constant fixture of the news cycle (Murray, 2017). Surprisingly, there is no universally accepted definition of a mass shooting (see Huff-Corzine & Corzine, 2020).…”
Section: Mass Shootings In the United Statesmentioning
confidence: 99%
“…Third, mental illness among these perpetrators is sometimes underestimated by those who cite research which used broad definitions of “mass violence” or “mass shootings,” instead of focusing on public mass shooters specifically. Public mass shooters are traditionally defined as perpetrators who killed four or more victims, unrelated to other criminal activity or “commonplace circumstance” (Krouse & Richardson, 2015, p. 10; Peterson & Densley, 2019a, p. 5) 5 . This refers to a rare and extreme type of killer who appears more likely to have mental health problems than other violent criminals (National Council of Behavioral Health, 2019).…”
Section: The Role Of Mental Illness In Mass Shootingsmentioning
confidence: 99%
“…First and foremost, data for this study came from The Violence Project’s Mass Shooter database (Peterson & Densley, 2019b), which attempted to identify all public mass shooters ( n = 171) in the United States from January 1, 1966 to October 1, 2019, based on the definition put forth by the Congressional Research Service (Krouse & Richardson, 2015). According to this definition, mass shooters who murdered four or more victims in a single public incident would meet the inclusion criteria, while domestic mass shootings and shootings due to “underlying criminal activity or commonplace circumstance (armed robbery, criminal competition, insurance fraud, argument, or romantic triangle)” should be excluded (Krouse & Richardson, 2015, p. 10; Peterson & Densley, 2019a, p. 5).…”
Section: The Current Studymentioning
confidence: 99%
“…Research on interpersonal violence has found that while the overall rate of violent crime in the United States has decreased since the early 1990s (United States Department of Justice, Federal Bureau of Investigation, 2018), targeted mass shooting events (defined as four or more victims murdered with firearms within one event, at least some of which occurred in a public place, and which aren’t attributable to criminal activity) have increased in intensity (i.e., the number of victims per event) and frequency (i.e., the number of events per year) in the last 50 years (Peterson & Densley, 2019). Traditional law enforcement approaches to targeted violence have primarily been reactive, focusing on police response to active shooter incidents (Police Executive Research Forum, 2014).…”
mentioning
confidence: 99%